The Crowdfunding Service as an Area of Cooperation between Companies - Wieczerzycki, Marcin (Studia Oeconomica Posnaniensia, 2014)
The creation of new communication technologies, which produce a certain compromise between mass - and personal communication, has resulted in an empowerment of today's consumer, whose traditional role, as presented in marketing literature, was that of a passive actor reduced solely to reacting to producers' stimuli. The consumers of today are not only involved in co-producing the goods and services they themselves as well as others consume, but they also function as investors, supplying producers with capital. This phenomenon is known as crowdfunding. However, only a handful of companies have at their disposal the appropriate communication infrastructure and well-developed consumer communities to be able to engage in direct crowdfunding. This is the reason behind the recent advent of cooperation between companies and crowdfunding platforms, which give access to large numbers of consumer-investors and which function as intermediaries between the demand and supply sides of the whole process. Indirect crowdfunding is a fairly new phenomenon that has not yet been the subject of very many theoretical studies. The purpose of this paper is to identify the process of cooperation between companies in the crowdfunding market. The analysis is conducted within the framework of a network approach. The core actors are identifyed, as well as their role in transferring and transforming resources within a given network.